AN APPROACH TO THE DEVELOPMENT OF THE URBAN DESIGN “KARAOTOK”, HUTOVO BLATO NATURE PARK - Nevenko Herceg; Jaroslav Vego; Svjetlana Stanić-Koštroman (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta, 2021)
Spatial planning is a vital process for a rapid and successful development of projects related to wetland management, and thereby projects related to tourism. Tourist activities could provide a boost to the development of general understanding of wetlands and raise public awareness of the functions and the ecosystem services wetlands provide. The tourism economy could be a source of income and could provide employment opportunities in rural areas. However, tourists also have an impact on wetlands. Protected areas accessible to tourists require a comprehensive management. In order to ensure a harmonious relationship between tourism activities and environmental protection, when developing an urban design within a protected area, it is crucial to have a sensitive approach. The paper suggests an approach to the development of the Urban Design "Karaotok", within the Hutovo Blato Nature Park.